THE EFFECT OF ELECTRONIC WORD OF MOUTH (EWOM), PRICE AND BRAND IMAGE ON RE-PURCHASE INTENTION (A CASE STUDY OF CITILINK INDONESIA CONSUMER IN MALANG) - JODI WINDRAWAN PUTRA (Jurnal Ilmiah Mahasiswa FEB, 2018)
Nowadays, the low-cost carrier becomes more popular because the middle-lower segment of society shows more promising choice to travel by planes with an affordable price, for example Citilink Indonesia. The purpose of this research is to explain the factors which influence the Citilink customer’s repurchase intention. This research implements Electronic Word of Mouth (EWOM), brand image, and price as the independent variables that influence customer’s repurchase intention. This research applies explanatory research, and the data are collected by employing a survey method (questionnaires). The respondents comprised 180 customers who had purchased Citilink Indonesia minimum in one purchased. The research data and hypothesis are analyzed by using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The research findings mainly indicated that EWOM and brand image significantly and positively influence Citilink customer's repurchase intention. In conclusion, the more positive the EWOM from the Citilink Indonesia’s previous customer, the higher the repurchase intention. In line with it, the more positive (good) brand image of Citilink Indonesia, the higher the repurchase intention of the customers.Keywords: Electronic Word of Mouth (EWOM), Price, Band Image, Repurchase Intention